2006
DOI: 10.2992/0097-4463(2006)75[97:ansocs]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Chocoan Sturnira (Chiroptera: Phyllostomidae: Stenodermatinae) From Western Ecuador and Colombia

Abstract: A distinctive new species of sturnirine bat, Sturnira (Sturnira) koopmanhilli, new species (Chiroptera: Phyllostomidae: Stenodermatinae), is described from 49 specimens collected in the Pacific drainage of the western Andes, at 300-2000 m in western Ecuador and Colombia. This yellow-shouldered bat is endemic to this Chocoan region where it is known from nine localities in Ecuador (Esmeraldas and Chimborazo) and Colombia (Chocó, Valle del Cauca, and Nariño). This moderately large Sturnira species (forearm lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…Like other phyllostomid genera (i.e., Carollia [ Solari and Baker 2006 , Pacheco et al 2004 , Velazco 2013 ] and Platyrrhinus [ Velazco 2005 , Velazco and Patterson 2008 , Velazco et al 2010 ]), the diversity of Sturnira has grown substantially from recent revisionary studies ( Iudica 2000 , McCarthy et al 2006 , Velazco and Patterson 2013 ). Only 14 species were recognized in Sturnira in the last world checklist ( Simmons 2005 ), but since then, three new species have been described, Sturnira koopmanhilli McCarthy et al, 2006, Sturnira perla Jarrín-V & Kunz, 2011, and Sturnira sorianoi Sánchez-Hernández et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Like other phyllostomid genera (i.e., Carollia [ Solari and Baker 2006 , Pacheco et al 2004 , Velazco 2013 ] and Platyrrhinus [ Velazco 2005 , Velazco and Patterson 2008 , Velazco et al 2010 ]), the diversity of Sturnira has grown substantially from recent revisionary studies ( Iudica 2000 , McCarthy et al 2006 , Velazco and Patterson 2013 ). Only 14 species were recognized in Sturnira in the last world checklist ( Simmons 2005 ), but since then, three new species have been described, Sturnira koopmanhilli McCarthy et al, 2006, Sturnira perla Jarrín-V & Kunz, 2011, and Sturnira sorianoi Sánchez-Hernández et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Jones & Carter (1976) suggested S. oporaphilum and S. bogotensis to be valid species or subspecies related to S. ludovici. Anderson et al (1982), Koopman (1994), andMcCarthy et al (2006) regarded S. bogotensis as a junior synonym of S. oporaphilum. Pacheco & Patterson (1992) recognized S. oporaphilum, S. ludovici, and S. bogotensis as different species: however, they suggested that S. ludovici might simply represent a large geographic variant of S. oporaphilum, with Venezuelan populations referred to S. ludovici representing yet another variant.…”
Section: Introductionmentioning
confidence: 99%
“…A close relationship between S. lilium and S. luisi, on both morphological and genetic grounds was recognized, also reporting the presence of an undescribed species endemic to Ecuador, named as S. sp. A and currently known as S. koopmanhilli (McCarthy et al 2006). More recently, Iudica (2000), in his unpublished thesis, defined 17 species based on a partial sequence of the cytochrome b gene (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…CMNH, 112823" and "CMNH, 112822", which belong to the species being described herein) are independent lineages, endemic to Ecuador, and thus far have not been found in any other region in the Neotropics. Subsequently, McCarthy et al (2006) described species S. sp. A as S. koopmanhilli.…”
Section: Introductionmentioning
confidence: 99%